Fabrication of Iron or Cobalt-Doped Carbon-Based Catalysts for Oxygen Reduction Reaction Using Soy Protein As Specific Nitrogen Precursor - Guo1, Chaozhong; Tian1, Liangliang; Liao4, Wenli; Chen2, Changguo (Asian Journal of Chemistry, 2014)
We here design two kinds of non-precious metal electrocatalysts (Fe-SP/C900 and Co-SP/C900) for oxygen reduction reaction by thermally treating a mechanical mixture of soy protein powder, carbon black and iron chloride or cobalt chloride at 900 °C for 2 h under the N2 atmosphere. The linear sweep voltammetry is used to evaluate the oxygen reduction reaction catalytic activities of Fe-SP/C900 and Co-SP/C900. The oxygen reduction reaction onset potential of Fe-SP/C900 is about 0.10 V (vs. Hg/HgO) at a scan rate of 5 mV s-1 in 0.1 mol L-1 KOH solution and the catalytic activity of Fe-SP/C900 is much better than that of Co-SP/C900. The formation of oxygen reduction reaction-active sites of Fe-SP/C900 and Co-SP/C900 can be facilitated by metallic iron and cobalt, respectively, but the metallic iron may play a more important role in improving the formation of active sites, resulting in the enhanced oxygen reduction reaction catalytic activity of Fe-SP/C900. Present study will encourage researchers to produce new catalytic materials for oxygen reduction using bio-proteins as specific nitrogen precursors.